Minimally invasive surgery for superior mesenteric artery syndrome: a case report and literature review. Issue 1 (February 2016) - Cullis, Paul S; Gallagher, Maeve; Sabharwal, Atul J; Hammond, Philip
Introduction: Superior mesenteric artery syndrome is a rare condition characterised by nausea, vomiting, postprandial pain, anorexia and early satiety. Conservative management is tried initially, but if this fails, surgery is indicated. There are few reports in the literature concerning superior mesenteric artery syndrome in children, and fewer still managed surgically by minimally invasive means. Case presentation: A 12-year-old girl presented with weight loss, early satiety and vomiting after corrective scoliosis surgery. After upper gastrointestinal endoscopy, contrast study and computed tomography imaging, a diagnosis of superior mesenteric artery syndrome was made. Conservative management by nasojejunal feeding failed; therefore, a laparoscopic duodeno-jejunostomy was undertaken. At follow-up, her symptoms had improved. Conclusion: This report describes the youngest child to undergo laparoscopic duodeno-jejunostomy for superior mesenteric artery syndrome. Laparoscopic duodeno-jejunostomy appears to be the most widely employed and reliable minimally invasive approach to superior mesenteric artery syndrome with a high success rate and acceptably low complication rate.